The Factors Affecting Technological Innovation Capabilities on Malaysian SMEs & Universities - Hanan Subhi Obaid1 Mohammad Arab Al-Musawi2 Mohanad S. S. Abumandil3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The study mean objectives were to investigate technological innovation skills have become a crucial component (SMEs) in the industrial and service sector to deal with fierce competition also meet consumer needs. Due to the inconsistency of previous research findings on the antecedent factors that may influence these capabilities, the study set out to empirically investigate the relationships between entrepreneurial orientation, market orientation, absorptive capacity, and technological innovation capabilities among SMEs operating in Penang. Furthermore, the leadership style influences the interaction between the EO, MO, AC, and TIC. Furthermore, the assumptions and model development for this research were based on the resource-based perspective (RBV). Self-administered questionnaires were mailed to the owners of SMEs in Penang. The sample of the study of 432 innovative firms participated in this survey, with a response rate of 63.9 percent. This research employed partial least squares structural equation modelling to analyse the measurement model’s validity and reliability and test the correlations (PLS-SEM). The results of this study reveal that EO, MO, and AC impact TIC, with the LS regulating the interaction between EO, MO, AC, and TIC. The theoretical and practical contributions of this work would assist academics and specialists. The study’s flaws were reviewed, and some helpful suggestions for future research work were given. Furthermore, the findings have important implications for practitioners working to establish and improve their firms’ competitive strategies in the hyper-competitive SMEs environment. This finding will help government departments develop new policies to support strategic plans, boost performance and contribution to GDP, which will generate jobs, and stimulate the growth of SMEs to achieve global competitiveness, all of which are primary goals of Penang’s industry’s strategic plan.